Sensitivity analysis from single-well ERT simulations to image CO2 migrations along wellbores - Picotti, Stefano (2013)
CO2 plume imaging is a required step in CO2 geological storage for both performance assessment and risk management purposes. This work has been performed in the frame of the CO2CARE project, its aim is to develop tools and methodologies to monitor CO2 migration and verify the long-term well integrity after site abandonment. The timely detection of an anomaly is essential to perform a suitable remediation. For this purpose, downhole tools are permanently installed, but it is important to check the resolution and efficiency of the adopted techniques. In particular, this study investigates the possibility of using electrical resistivity tomography (ERT) to image CO2 migrations around observation boreholes through a sensitivity study. © 2013 by The Society of Exploration Geophysicists.